A method to eliminate bromide interference on standard COD test for bromide-rich industrial wastewater. (February 2020) - Shi, Xueqing; Huang, Shujuan; Yeap, Tsuey Shan; Ong, Say Leong; Ng, How Yong
Abstract: Chemical oxygen demand (COD) is one of the most important water quality parameters that quantifies the amount of oxygen needed to oxidize oxidizable pollutants (mainly organics) in water samples. However, erroneous COD results were commonly observed for bromide-rich industrial wastewater samples using standard COD test. Bromide in water sample is known to seriously interfere with COD test. However, there is no satisfactory approach to effectively eliminate bromide interference thus far. In this study, two strategies, namely masking and correction, were investigated for their effectiveness to suppress bromide interference. For the masking strategy, silver ion was assessed for its effectiveness to neutralize bromide in water samples through precipitation and complex formation reactions. Silver ion offered only partial masking effect on bromide, while the residue bromide can still cause significant interference on COD determination. For the correction strategy, an equivalent redox reaction reflecting bromide interference mechanism was proposed, and a theoretical correction factor of 0.1 g COD/g Br − was found based on stoichiometry. The effectiveness of the proposed correction factor for bromide interference under different wastewater pollutant matrix was evaluated using different types of wastewater samples (synthetic wastewater, domestic wastewater and bromide-rich industrial wastewater) with varying amounts of bromide (from 0 to 2000 mg L −1 ) added to the samples. The findings showed that with bromide concentration up to 600 mg L −1, the correction factor of 0.1 g COD/g Br − was applicable to all the tested wastewater samples, suggesting that this correction strategy could be practically used to eliminate bromide interference in standard COD test. Graphical abstract: Image 1 Highlights: Two strategies assessed to eliminate bromide interference on standard COD test. Silver ion showed partial masking effect to suppress bromide interference. A theoretical correction factor proposed based on reaction stoichiometry. Correction factor could be practically applied to eliminate bromide interference.